PENGETAHUAN IBU HAMIL TENTANG STUNTING DI KLINIK BIDAN MESRA, AM,KEB KOTA PADANGSIDIMPUAN TAHUN 2020 - ELVI SURYANI (JURNAL ILMIAH KOHESI, 2021)
The prevalence of stunting in Indonesia is higher than in other countries, in Southeast Asia, such as Myanmar (35%),Vietnam (23%), Malaysia (17%), Thailand (16%), and Singapore (4%). The purpose of this research is to study theknowledge of pregnant women about stunting in the midwife Am Am Keb Clinic in Padangsidimpuan in 2020. This type ofresearch is descriptive using acedental samples with 20 respondents. Data collection uses questionnaire sheets, data onknowledge, age, education, occupation, parity, and information sources. Based on the results of research from 20respondents, gathered a level of insufficient knowledge, namely 14 people (70%), based on the age gained less, namely 11people (55%), based on education gained less, namely 8 people (40%), based on the results the study found less, namely10 people (50%), based on lack of parity, namely 13 people (65%), and based on sources of information collected less,namely 7 people (35%). Based on the results of the study it can be concluded that the knowledge of pregnant women aboutstunting is still lacking, so it is expected that mothers will increase knowledge about stunting through health workers, printmedia, and electronic media.